2022
DOI: 10.7150/ijbs.70335
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 promotes cell cycle progression via m6A/YTHDF1-dependent regulation of CDC25B translation

Abstract: The cell cycle machinery controls cell proliferation and the dysregulation of the cell cycle lies at the heart of carcinogenesis. Thus, exploring the unknown regulators involved in the cell cycle not only contribute to better understanding of cell proliferation but also provide substantial improvement to cancer therapy. In this study, we identified that the expression of methyltransferase METTL3 was upregulated in the M phase. Overexpression of METTL3 facilitated cell cycle progression, induced cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…However, in this study, we found that YTHDF1 also bound to Cdh2 mRNA, and knockdown of Ythdf1 also led to decreased N-cadherin expression. Cumulative studies have shown that YTHDF1 is responsible for the translation of target genes via m 6 A [ 32 35 ]. Therefore, we speculated that both the IGF2BP1/2/3 complex and YTHDF1 in Sertoli cells are involved in the regulation of Cdh2 mRNA translation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, we found that YTHDF1 also bound to Cdh2 mRNA, and knockdown of Ythdf1 also led to decreased N-cadherin expression. Cumulative studies have shown that YTHDF1 is responsible for the translation of target genes via m 6 A [ 32 35 ]. Therefore, we speculated that both the IGF2BP1/2/3 complex and YTHDF1 in Sertoli cells are involved in the regulation of Cdh2 mRNA translation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, METTL3 exerts oncogenic effects by promoting aerobic glycolysis. METTL3 and CDC25B were highly expressed in cervical cancer [ 80 ]. METTL3 induced CDC25B mRNA m6A modification in a YTHDF1-dependent manner and enhanced the tumorigenicity of CC cells in vivo [ 80 ].…”
Section: Role Of Mettl3 In Cancermentioning
confidence: 99%
“…The m6A “readers” can selectively recognize the m6A methylation modifications in the target RNA, and participate in various of stages of RNA metabolism ( Zhang and Su, 2022 ). “Readers” include proteins containing YTH domains (YTHDF1/2/3 and YTHDC1/2), heterogeneous ribonucleoproteins including heterogenous nuclear ribonucleoprotein (HNRNP) C (HNRNPC), G (HNRNPG), and A2B1 (HNRNPA2B1), and insulin-like growth factor 2 binding proteins (IGF2BPs), which are members of a protein family closely associated with several ageing diseases ( Li et al, 2022c ; Li et al, 2022d ). Different “readers” have different cellular localizations and thus perform multiple biological functions ( Li et al, 2022d ).…”
Section: The Current Sight Of M6a Modificationsmentioning
confidence: 99%
“…Different “readers” have different cellular localizations and thus perform multiple biological functions ( Li et al, 2022d ). YTH domain family protein 1 (YTHDF1) initiates RNA translation by interacting with the translation initiation factors and ribosomes, whereas the YTH domain family protein 2 (YTHDF2) selectively binds to m6A modified transcripts and promotes their degradation ( Li et al, 2022c ). YTHDF1/2 and YTHDF3 play synergistic roles in promoting YTHDF1-mediated translation and suppress YTHDF2-mediated m6A modification ( Li et al, 2022d ).…”
Section: The Current Sight Of M6a Modificationsmentioning
confidence: 99%